2017
DOI: 10.1055/s-0037-1603674
|View full text |Cite
|
Sign up to set email alerts
|

Transient Common Peroneal and Tibial Nerve Palsy Following Knee Arthroscopy for the Treatment of Discoid Lateral Meniscus

Abstract: The number of knee arthroscopies has increased rapidly since the 1980s and are among the most common orthopedic procedures today. It is generally considered a minimally invasive surgery with relatively low morbidity, but it is not without risk of complications. We report the case of a 14-year-old boy who developed a lesion of common peroneal nerve and tibial nerve after knee arthroscopy for a torn discoid lateral meniscus, which was confirmed by electromyogram study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Large cohort studies report overall knee arthroscopy complications to range from 0.6% to 8.2%. 46,47 More recent data identified knee arthroscopy surgical related complications in 3.7%. 48 Incidence of iatrogenic peripheral nerve injuries has been reported up to 0.6%, with saphenous nerve injuries being the most common.…”
Section: Kneementioning
confidence: 99%
See 1 more Smart Citation
“…Large cohort studies report overall knee arthroscopy complications to range from 0.6% to 8.2%. 46,47 More recent data identified knee arthroscopy surgical related complications in 3.7%. 48 Incidence of iatrogenic peripheral nerve injuries has been reported up to 0.6%, with saphenous nerve injuries being the most common.…”
Section: Kneementioning
confidence: 99%
“…Large cohort studies report overall knee arthroscopy complications to range from 0.6% to 8.2% 46,47. More recent data identified knee arthroscopy surgical related complications in 3.7% 48.…”
Section: Kneementioning
confidence: 99%
“…Injuries involving direct trauma to the nerves caused by intraoperative, direct posterior capsular violations,[ 18 , 20 , 24 ] posterior trocar placement,[ 14 ] or closed traction during intra-operative knee manipulation. [ 3 , 11 ] However, no study was identified to describe secondary tibial nerve injuries following a postoperative pseudoaneurysm. During knee arthroscopic surgeries, vessel violations are usually related to the popliteal artery.…”
Section: Discussionmentioning
confidence: 99%
“…We present two secondary tibial nerve injuries following ACLR as a long-term complication. e delayed diagnosis of popliteal Although ACLR is considered a safe procedure with low complication rates, [7] several studies [3,11,14,18,20,24] have already described iatrogenic common peroneal and tibial nerve injuries. Injuries involving direct trauma to the nerves caused by intraoperative, direct posterior capsular violations, [18,20,24] posterior trocar placement, [14] or closed traction during intra-operative knee manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Bernardi and Tudisco reported a case of iatrogenic lesion of the common peroneal and tibial nerves caused by arthroscopy caused by the violation of the posterolateral angle by motorized arthroscopic instrumentation during the attempt to remove an osteochondral free body and a patient positioning case related to nerve traction during surgery. 13 SHOULDER Shoulder arthroscopy allows operating inside the joint through 2 to 4 small holes avoiding large incisions. Still, despite the indisputable advantages of less invasiveness and quicker functional and joint recovery time, this method is not without risk of complications related to the specific procedure.…”
Section: Knee (Fig2)mentioning
confidence: 99%